Post Un-Lock From Territorial Vulnerabilities to Local Resilience - Brunetta, Grazia; Lombardi, Patrizia; Voghera, Angioletta (The Urban Book Series, 2023)
This open access book builds a framework that holds together numerous open issues in territorial planning: from the understanding of territorial, landscape, environmental and climatic dynamics to the analysis of local vulnerabilities, to the use of modern survey techniques to support planning. What is the role of urban and regional planning in achieving the sustainable development goals of our communities considering the major issues posed by the COVID-19 pandemic in urban planning? And how do these medium- and long-term objectives interact with the needs that the emergency has given rise to? Post Un-Lock-from territorial vulnerabilities to local resilience-aims to provide the reader with a useful key to understand how the COVID-19 pandemic can be seen as a catalyst for a restart based on the concepts of sustainability and resilience. In fact, the COVID-19 experience evidences the need to propose a planning system able to integrate multiple scales according to an interdisciplinary approach focused on in-depth knowledge of the territorial risks and vulnerabilities. Besides, with the contribution of the new technologies, it is able to rethink spaces on a neighbourhood scale, conceived as a "local resilience unit" that ensures the population high standards of safety, liveability, and accessibility to proximity services. In this view, planning is increasingly concerned about social aspects and the well-being of communities, supported by indicators and evaluation tools. With the proposal of the concept of local resilience unit, Post Un-Lock takes a step forward towards the definition of a new paradigm of local planning and a topic for urban regeneration.